Degradation of Aluminide Layers During Cyclic Oxidation of Ferritic 430 Stainless Steel - Mohammad Badaruddin (Institute of Research and Community Outreach, Petra Christian University, 2011)
In order to increase the performance of the preferred Ferritic 430 SS for manufacturing automobile and motor-cycle exhaust systems. The aluminizing coating on the surface of bare steel was applied by hot-dipping method in a molten pure aluminum. The high temperature oxidation of the aluminized steel was cyclically studied at 900 °C and 1000 °C in static air. The degradation of intermetallic layers during cyclic oxidation were analyzed by means of X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). The crack perpendicular to the specimen surface rapidly propagated through the FeAl and Fe3Al layers due to a thermal expansion mismatch upon cooling to room temperature. The accumulation of voids generated crack at the interface between the aluminide layer and the steel substrate. Oxygen is allowed to penetrate into the aluminide layer crack, rapidly forming alumina oxide and closing the crack. Some of the aluminide layers peeled off due to this rapid growth. Thus, the protective Al2O3 layer degraded and later, the substrate was oxidized subsequently to form iron-rich oxide (Fe2O3) at 1000 °C.